2001
DOI: 10.1128/jvi.75.23.11791-11802.2001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Zyxin, a Focal Adhesion Protein, with the E6 Protein from Human Papillomavirus Type 6 Results in Its Nuclear Translocation

Abstract: Zyxin, a focal adhesion molecule, interacts specifically with the E6 protein from human papillomavirus (HPV) type 6 in a yeast two-hybrid screen of a cDNA library prepared from human keratinocytes. Zyxin does not interact significantly with E6 proteins from HPV types 11, 16, or 18. The interaction was confirmed by in vitro and in vivo analyses and it requires the LIM domains (Lin-11, Isl-1, and Mec-3 [G. Freyd, S. K. Kim, and H. R. Horvitz, Nature 344:876-879, 1990]) found at the carboxyl terminus of zyxin. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 81 publications
2
44
0
Order By: Relevance
“…A diffusion-like mechanism seems inefficient within a crowded cytoplasmic environment, and transport along the flux of actin filaments may serve as a much more effective mechanism. Particularly relevant is the relocation of zyxin from focal adhesions into the nucleus of vascular smooth muscle cells in response to mechanical signals, where zyxin itself may serve as a transcription activator (Degenhardt and Silverstein, 2001). In addition, retrograde flux of FAK may have a profound effect on the state of phosphorylation at focal adhesions and actin filaments, which in turn affects the maturation and turnover of focal adhesions (Webb et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diffusion-like mechanism seems inefficient within a crowded cytoplasmic environment, and transport along the flux of actin filaments may serve as a much more effective mechanism. Particularly relevant is the relocation of zyxin from focal adhesions into the nucleus of vascular smooth muscle cells in response to mechanical signals, where zyxin itself may serve as a transcription activator (Degenhardt and Silverstein, 2001). In addition, retrograde flux of FAK may have a profound effect on the state of phosphorylation at focal adhesions and actin filaments, which in turn affects the maturation and turnover of focal adhesions (Webb et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies further indicated that mechanical stimulation can induce the change in distribution of zyxin from focal adhesions to either actin stress fibers in cultured fibroblasts (Yoshigi et al, 2005), or the nucleus of vascular smooth muscle cells (Cattaruzza et al, 2004). The latter may be related to the suspected ability of zyxin to regulate gene expression (Degenhardt and Silverstein, 2001). However, the mechanism of redistribution from focal adhesions is unclear, because these studies showed only the steady-state localization after mechanical stimulation.…”
mentioning
confidence: 99%
“…The first well-characterized activity of E6 was to bind to and accelerate the degradation of the p53 tumor suppressor, 2 but E6 also interacts with a number of additional cellular proteins that are engaged in a variety of cellular processes. These include proteins involved in the regulation of transcription, DNA replication and proliferation such as p300/CBP, 3,4 IRF-3, 5 hMcm 7, 6,7 E6TP1, 8 ADA3, 9,10 TRIP-Br1 11 and tuberin 12 ; proteins involved in apoptosis and immune evasion such as Bak, 13 c-Myc, 14,15 tumor necrosis factor (TNF) R1 16 and FADD 17 ; proteins involved with epithelial organization and differentiation such as paxillin, 18 E6BP/ERC-55, 19 zyxin 20 and fibulin-1; 21 proteins involved in cell-cell adhesion, polarity and proliferation control that contain a PDZ-binding motif such as hDLG, 22,23 hScrib, 24 MAGI-1, 25,26 MAGI-2, MAGI-3 27 and MUPP1; 28 and proteins involved in DNA repair such as XRCC1 29 and 6-O-methylguanine-DNA methyltransferase. 30 However, with some exceptions, the mechanisms and consequences of the interactions between E6 and its cellular partners for either the host or the virus are not well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…12). Identified E6 partners include the following: proteins involved in the regulation of transcription and DNA replication, such as p300/CBP (13,14), , hMcm7 (16,17), E6TP1 (18), and ADA3 (19,20); proteins involved in apoptosis and immune evasion such as Bak (21), c-Myc (22), and TNF receptor 1 (TNF R1) (23); proteins involved with epithelial organization and differentiation such as paxillin (24), E6BP/ERC-55 (25), zyxin (26), HPV 6 and fibulin-1 (27); proteins involved in cell-cell adhesion, polarity, and proliferation control that contain a PDZ-binding motif such as hDLG (28,29), hScrib (30), MAGI-1 (31,32), MAGI-2, MAGI-3 (33), and MUPP1 (34); and proteins involved in DNA repair such as XRCC1 (35) and 6-O-methylguanine-DNA methyltransferase (36). However, with some exceptions, the mechanisms and the consequences of the interactions between E6 and its reported cellular partners on either the host or the virus life cycle are not well understood.…”
mentioning
confidence: 99%